Pengembangan Gamifikasi Scratch Berbasis MDLC untuk Meningkatkan Computational Thinking pada Pembelajaran Algoritma dan Pemrograman SMK - Sri Mulyani Nst; Resmi Darni; Mahesi Agni Zaus; Rizkayeni Marta (TIN: Terapan Informatika Nusantara, 2026)
Students' Computational Thinking skills in Algorithms and Programming materials are still relatively low because the use of technology-based interactive learning media is not optimal. This study aims to develop gamification-based learning media using Scratch and test its feasibility and practicality in learning. The research method used is Research and Development (R&D) with the Multimedia Development Life Cycle (MDLC) model which includes the stages of concept, design, material collecting, assembly, testing, and distribution. The study was conducted at SMK Muhammadiyah 1 Padang with 35 class X students in Informatics as subjects. Data collection was carried out through expert validation, practicality questionnaires, and pretest and posttest tests. The initial practicality test was conducted on 15 students as a small group which is part of the total research subjects before implementation on all subjects. The validation results by three media experts showed a percentage of 93.7% with a very feasible category. The results of the practicality test obtained a percentage of 96% with a very practical category. The results of the Computational Thinking ability measurement showed an average pretest score of 7.71 (48.2%) and a posttest score of 12.6 (78.75%) with an N-Gain value of 0.59 which is in the moderate category. These findings indicate an increase in students' Computational Thinking abilities after using the developed media. This study produced a gamification-based learning media using Scratch that has been declared valid with a very feasible and practical category for use in learning. In addition, the results of the media implementation showed an increase in students' Computational Thinking abilities with a moderate increase category. The results of this study contribute as an alternative interactive learning media that can be used by teachers in Informatics learning, especially in Algorithm and Programming materials at the vocational high school level.